Dusting Hole Film Cooling Heat Transfer on a Transonic Turbine Blade Tip. (6th October 2022) - Manneschmidt, Ward; Collopy, Hallie; Ligrani, Phillip; Goethals, Kyle; Cox, Matthew; Xu, Hongzhou; Fox, Michael
Abstract : Investigated is a transonic turbine blade tip with a squealer rim and a squealer recess, with a single dusting film cooling hole contained within the leading edge region of the squealer recess. Data are provided for transonic flow conditions for a range of film cooling blowing ratios for two tip gap values, using a linear cascade, with no relative motion between the blade and the casing. Surface heat transfer characteristics are measured using the transient impulse-response measurement approach, employed with infrared thermography. Line-averaged adiabatic film cooling effectiveness values, for the 1.4 mm tip gap, are generally very small along the pressure side rim, with only small, locally increased values along the suction side rim. For the 0.8 mm tip gap, line-averaged adiabatic film cooling effectiveness values are generally somewhat higher along the pressure side rim and along the suction side rim. In general, effectiveness values for both tip gap values, for these locations, and for the recess region, increase as the blowing ratio increases. As the tip gap decreases from 1.4 mm to 0.8 mm, line-averaged adiabatic film cooling effectiveness generally increases on the rims and downstream regions of the recess, with increased magnitudes which are spread over larger spatial surface areas. For tip gaps of 0.8 mm and 1.4 mm, for regions where the line-averaged heat transfer coefficient ratio deviates significantly from 1.00, values generally decrease as the blowing ratio increases. Across every region of the blade, line-averaged heat transfer coefficient ratios either decrease or remain approximately invariant, as the tip gap value decreases from 1.4 mm to 0.8 mm.